2020
DOI: 10.1016/j.clay.2020.105442
|View full text |Cite
|
Sign up to set email alerts
|

Identification of montmorillonite particle edge orientations by atomic-force microscopy

Abstract: Statistical information on the edge surface area and edge crystallographic orientation of clay nanoparticle surfaces is essential for proper accounting of the protonation-deprotonation reactions as a part of mechanistic surface complexation models. A combination of atomic-force microscopy (AFM) measurements and molecular dynamics computer simulations made it possible to quantify the relative contributions of the most frequently occurring montmorillonite edge surfaces to the total edge surface area. Edge surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 59 publications
4
18
0
Order By: Relevance
“…All other parameters were obtained from direct measurements or independent models such as first principle molecular dynamics (FPMD). ,, In the proposed electrostatic model, an important assumption is the crystalline nature of clay edge surfaces for which a structure identical to the bulk layer structure was considered to calculate protonation–deprotonation reaction constant using FPMD techniques. , , Our HR-STEM results provide a strong case of the adequacy of the crystallinity assumption. Besides, recent atomic force microscopy measurements enabled to quantify the preferential orientation of Kunipia montmorillonite edge surfaces, and results were in good agreement with the average orientation considered in our model. While these findings support the adequacy of the proposed model, the number of possible site combinations for Pb 2+ , Mg 2+ , and Zn 2+ adsorption makes it impossible to warrant unicity of the model parameters, and different combinations of adsorption and log K values may be as effective as the set of parameters fitted in this study.…”
Section: Modeling and Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…All other parameters were obtained from direct measurements or independent models such as first principle molecular dynamics (FPMD). ,, In the proposed electrostatic model, an important assumption is the crystalline nature of clay edge surfaces for which a structure identical to the bulk layer structure was considered to calculate protonation–deprotonation reaction constant using FPMD techniques. , , Our HR-STEM results provide a strong case of the adequacy of the crystallinity assumption. Besides, recent atomic force microscopy measurements enabled to quantify the preferential orientation of Kunipia montmorillonite edge surfaces, and results were in good agreement with the average orientation considered in our model. While these findings support the adequacy of the proposed model, the number of possible site combinations for Pb 2+ , Mg 2+ , and Zn 2+ adsorption makes it impossible to warrant unicity of the model parameters, and different combinations of adsorption and log K values may be as effective as the set of parameters fitted in this study.…”
Section: Modeling and Discussionsupporting
confidence: 82%
“…The crystallographic orientation of the edge surfaces and the existence of various functional groups on these surfaces are fundamental assumptions of the model. Theoretical calculations predicted that the most abundant edges surfaces are perpendicular to [010] and [110] crystallographic directions. This preferred orientation was evidenced recently by direct observations using AFM techniques . The crystalline nature of clay mineral edge surfaces is another prerequisite to the applicability of the model that builds on an edge surface structure that is identical to the structure of the inner layer.…”
Section: Theoretical Backgroundmentioning
confidence: 95%
See 1 more Smart Citation
“…Several recent studies have demonstrated a very good agreement of the 2-D and 3-D interfacial aqueous solution structures at heterogeneously charged basal and edge surfaces of clay nanoparticles simulated with Clayff with results from experimental atomic force microscopy (AFM) observations. These studies illustrate the value of using molecular simulations as a tool in the atomistic-scale interpretation of complex AFM results.…”
Section: Advances In Clayffmentioning
confidence: 80%
“…Two main approaches have been developed to characterize clay particles’ aspect ratio : direct electron and close field microscopy image analysis and indirect methods relying on the detection of molecular probe interaction with the surface domains. The latter group of methods mainly includes measurements of high-resolution Ar or N 2 adsorption isotherms at 77 K (derivative isotherm summationDIS) , and adsorption microcalorimetry analysis. , They allow monitoring of the adsorbed amount variation with pressure and thermal effects of adsorption, respectively, upon progressive coverage of the structurally and energetically heterogeneous clay surface with probe molecules.…”
Section: Introductionmentioning
confidence: 99%